Morphological Error Analysis in Students' Explanatory Text : An Analysis Based on Gender - Moh Tahir; Hardianty Rahayu; Ali Ali; Idris Idris; Gusti Ketut Alit Suputra (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the form of morphological errors in student explanatory text based on gender. This research was a multi-case study with a qualitative approach. This study's type of data was written from the explanatory essays of 78 students from three junior high schools in Palu. Data was collected using the listening method obtained from collecting student assignments using reading and note-taking techniques. Data analysis in this study used four methods, namely 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion drawing. Presentation of the results of data analysis using informal methods. Based on the study's results, morphological errors were found in the explanatory essays of Grade VIII students. The errors referred to 1) Affixation Errors (13 errors), 2) Reduplication Errors (18 errors), and 3) Compound Errors (6 errors). Both genders made similar mistakes regarding abbreviating morphs and compounding but differ regarding affixation and reduplication. Female students made more affixation errors, specifically omission errors. Meanwhile, male students made more reduplication errors. Morphological errors in students' explanatory essays can serve as a barometer for improving comprehension of good Indonesian. Morphological errors in students' explanatory essays can be a benchmark for increasing understanding of good Indonesian rules.